2018
DOI: 10.1016/j.ymthe.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Triple Vectors Expand AAV Transfer Capacity in the Retina

Abstract: Retinal gene transfer with adeno-associated viral (AAV) vectors holds great promise for the treatment of inherited retinal degenerations (IRDs). One limit of AAV is its transfer capacity of about 5 kb, which can be expanded to about 9 kb, using dual AAV vectors. This strategy would still not suffice for treatment of IRDs such as Usher syndrome type 1D or Alström syndrome type I (ALMS) due to mutations in CDH23 or ALMS1, respectively. To overcome this limitation, we generated triple AAV vectors, with a maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 85 publications
1
98
0
Order By: Relevance
“…The correct reassembly of the full-length expression cassette in the nuclei of target cells results in the production of full-length mRNA and protein (Yan et al, 2000;Duan et al, 2001;Chamberlain et al, 2016). To date, dual-and triple-AAV vectors have demonstrated efficacy in photoreceptors and muscle cells (Duan et al, 2001;Ghosh et al, 2008;Trapani et al, 2014;Maddalena et al, 2018), but have not been established for IHCs.…”
Section: Introductionmentioning
confidence: 99%
“…The correct reassembly of the full-length expression cassette in the nuclei of target cells results in the production of full-length mRNA and protein (Yan et al, 2000;Duan et al, 2001;Chamberlain et al, 2016). To date, dual-and triple-AAV vectors have demonstrated efficacy in photoreceptors and muscle cells (Duan et al, 2001;Ghosh et al, 2008;Trapani et al, 2014;Maddalena et al, 2018), but have not been established for IHCs.…”
Section: Introductionmentioning
confidence: 99%
“…This group also tested an AAV8 serotype and found that there was more expression of the transgene in photoreceptors when compared to AAV2 serotypes. In the case of USH 1D (CDH23 mutation) and Alström syndrome type 1 (ALMS1 mutation), larger payloads are necessary, and recently triple AAV vector strategies have allowed transfer capacities up to about 14 kb, albeit with substantially reduced photoreceptor transduction efficiencies . Further investigation will be needed to determine the utility of dual and triple vectors for delivering larger genes into the eyes.…”
Section: Future Directions To Increase Efficacy Of Therapymentioning
confidence: 99%
“…In the case of USH 1D (CDH23 mutation) and Alström syndrome type 1 (ALMS1 mutation), larger payloads are necessary, and recently triple AAV vector strategies have allowed transfer capacities up to about 14 kb, albeit with substantially reduced photoreceptor transduction efficiencies. 120 Further investigation will be needed to determine the utility of dual and triple vectors for delivering larger genes into the eyes. If their reduced transduction efficiencies cannot be overcome, alternative methods such as viral vectors with larger capacities like lentiviruses, or gene editing techniques such as CRISPR/Cas strategies may be employed; however, both involve risks of direct alteration of the host genome.…”
Section: Vector Improvementmentioning
confidence: 99%
“…Furthermore, MAP-ENVIVIDERS also provides great potential to facilitate the coexpression of multiple genes and reduce the harmful effects for clinical gene therapy [51][52][53][54][55][56] . labeling.…”
Section: Map-envividersmentioning
confidence: 99%